2020
DOI: 10.1248/bpb.b20-00124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Kidney Disease on Hepatic Clearance of Drugs in Rats

Abstract: The pharmacokinetics of some hepatically cleared drugs have been reported to fluctuate in patients with renal impairment, but the definitive factors have not been clarified. We compared the pharmacokinetics of some drugs with different hepatic elimination processes in a chronic kidney disease (CKD) rat model, to optimize their administration during kidney injury. We chose indocyanine green (ICG), midazolam (MDZ), and acetaminophen (APAP) as reference drugs to determine changes in hepatic clearance pathways in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(46 reference statements)
1
1
0
Order By: Relevance
“…We observed that mice either co-treated or pre-treated with adenine neither exhibited histologic evidence of liver damage nor elevated ALT levels, suggesting that adenine was not toxic to the liver. Our results support findings from other studies showing a lack of adenine hepatotoxicity ( 42 , 43 ). However, another study reported a hepatotoxic effect of adenine as demonstrated by elevated liver enzymes in response to inflammation ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…We observed that mice either co-treated or pre-treated with adenine neither exhibited histologic evidence of liver damage nor elevated ALT levels, suggesting that adenine was not toxic to the liver. Our results support findings from other studies showing a lack of adenine hepatotoxicity ( 42 , 43 ). However, another study reported a hepatotoxic effect of adenine as demonstrated by elevated liver enzymes in response to inflammation ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…We observed significantly higher concentrations of paracetamol and glucuronide conjugate in patients with renal dysfunction. Renal dysfunction has been observed to result in reduced hepatic clearance by an extent of around 30% [25]. Sulfation pathway has been shown to be saturable at therapeutic doses and so sulphate conjugates have been debated to play a limited role in hepatotoxicity [26].…”
Section: Comparison With the Existing Literaturementioning
confidence: 99%